Exchange Rate Pass-Through (ERPT) and its Implications for Vietnam: Vector Autoregressive Approach from Vietnam-Korea Trade Data - Huong, DO Thi My; Minh, CAO Hong (Asian Economic and Financial Review, 2019)
This article investigates the exchange rate pass-through (ERPT) into Vietnam’s import price and consumer price index employing the trade data between Vietnam and Korea for the period from Jan 2008 – March 2017 on a monthly basis. From the empirical outcome of the Vector Autoregressive (VAR) model, the ERPT coefficients for import price are quite low and statistically insignificant, which implies that the price of importing goods from Korea might depend mainly on other factors rather than KRW/VND exchange rate. On the contrary, the transmission from exchange rate to Vietnam’s consumer price index is so complete that a 1% shock in exchange rate can cause a change by 0.994% in consumer price index at lag order 2. This result is further confirmed by variance decomposition and Granger causality tests which reveal that the exchange rate shock builds the strongest influence on the fluctuation of Vietnam’s inflation rate.